New species and new records of Coryphorus Peters, 1981 (Ephemeroptera: Coryphoridae) from Brazil - Lima, Lucas R. C.; Nascimento, Stênio R. S.; Boldrini, Rafael (Zootaxa, 2018)
A new species Coryphorus is presented,  based on recent collections from Northeastern Brazil and specimens deposited in the Museu Regional de Entomologia da Universidade Federal de Viçosa (UFVB) and Coleção Zoológica da Universidade Federal de Roraima (UFRR). Coryphorus molinerii sp. nov. is described based on male imagos and can be distinguished by the penis with rounded margins and forceps with segment II narrow and sharpening towards apex. Besides, C. aquilus Peters, (1981) is reported for Tocantins State for the first time.